Pollution reduction and electricity production from dairy industry wastewater with microbial fuel cell - D. Sivakumar (Global Journal of Environmental Science and Management)
Taguchi L9 orthogonal array was implemented to select optimum values of process parameters and to attain the maximum removal of pollutants and power generation from dairy industry wastewater using double chambered salt bridge microbial fuel cell. The maximum chemical oxygen demand reduction, current, voltage, power, current density and power density in double chambered salt bridge microbial fuel cell from dairy industry wastewater was found to be 86.30 %, 16.10 mA, 886.34 mV, 14.27 mW, 1219.69 mA/m2 and 1081.06 mW/m2 respectively for the optimum value of 1M NaCl concentration, 10 % agar concentration and 0.10 m salt bridge length. Double chambered salt bridge microbial fuel cell was not only removed chemical oxygen demand and produced power, but it also removed other pollutants at the maximum level against the best optimum value of process parameters from the dairy industry wastewater. The proposed regression model was used to select the right combination of process parameters for obtaining a maximum reduction of pollutants and simultaneous power production from the dairy industry wastewater.